PENGARUH STRES KERJA DAN KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA ANGGOTA POLRI DI POLDA SUMATERA SELATAN - Andes Purwanti; Zunaidah Zunaidah; Yuliansyah M Diah; Marlina Widiyanti (UNIB Press, 2020)
The purpose of this study was to determine the effect of work stress and transformational leadership both partially and simultaneously on the performance of Polri Members in the South Sumatra Regional Police. The subjects in this study were members of the National Police at the South Sumatra Regional Police. The sample in this study were 96 people. Data collection techniques were carried out using a questionnaire. The statistical analysis technique used is multiple linear regression test, F test and t test. Based on the results of the study indicate that together and partial work stress and transformational leadership have a significant influence. This is based on the results of the F test (Simultaneous Test) with the significance value obtained is 0,000 <0.05. Based on the results of the t test showed work stress (X1) partially significant effect on the Performance of Police Members in the South Sumatra Regional Police (Y) with a significance value of 0.044 <0.05. Furthermore, the transformational leadership variable (X2) partially also had a significant effect on the performance of Polri Members in the South Sumatra Regional Police (Y) with a significance value of 0,000 <0.05.